The Correlation of Self-Care Practices in the Online Learning Environment of Teacher Education Students - Panganiban, Teejay D.; Adalla, John Marvin D.; Ontreras, Anna Mariz T.; Javier, Abegail Joy M. (Community and Social Development Journal, 2025)
This research examined the self-care practices in online learning among teacher education students during the Academic Year 2021-2022. Specifically, it investigated the significant relationship between the respondents' profiles and their self-care practices in online learning. Data were collected using a questionnaire as the principal tool. The gathered data were analyzed using appropriate statistical tools, including correlation analysis. The results indicated that the respondents were largely female, mostly enrolled in the Bachelor of Secondary Education program, belonging to the Superior Group, and from middle-income families. Additionally, the study found that self-care practices were generally maintained at a good level despite the challenges posed by the pandemic. Chi-square analysis revealed significant relationships between self-care practices and variables such as sex, academic program, birth order, and socio-economic status. Based on these findings, the study recommends the use of infographic materials to promote good self-care practices in online learning among students.